ANALISIS STRATEGI KOMUNIKASI PEMASARAN DI BEVERLY HOTEL BATAM - Kurnia, Okki; Tcan, Erwina; Nasution, Nadia widari; Cherryline Simatupang, Violetta; Budiartha, I Nyoman (Puslitabmas Batam Tourism Polytecnic, 2024)
The purpose of marketing communications is to inform, persuade and remind. However, some of the communications delivered were not in accordance with the intended purpose, causing problems. The purpose of this study was to find out how the marketing communication carried out by Beverly Hotel Batam. This research is based on Hermawan's theory of marketing communication with 5 indicators (promotion, advertising, personal selling, public relations, direct marketing). This research was conducted using qualitative research methods. Data collection techniques were carried out through observation, literature study, and interviews with hotel general managers, senior sales and marketing, and front office manager. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of the analysis show that the application of marketing communications at Beverly Hotel Batam is quite good in terms of indicators (promotion, advertising, personal selling, public relations, direct marketing). Based on the results of the analysis, it is expected that Beverly Hotel Batam can improve its human resources and consider conducting training for the front office and sales and marketing departments.